ICP analysis of heavy metals in Meretrix SPP from Pantai Sepat, Kuantan, Pahang / Nurul Izzah Humairah Sharrudin … [et al.] - Sharrudin, Nurul Izzah Humairah; Md Isa, Nurun Nadhirah; Nawi, Liliwirianis; Mohd Jan, Sarah Laila; Mohd Khazaai, Siti Noorhafiza (Universiti Teknologi MARA, Sabah, 2023)
Hard clams constitute the genus Meretrix is one of the most demanded bivalvia species in Malaysia. However, the unknown level of heavy metal content raises concerns for the health of seafood lovers, particularly those who consume seafood from Pantai Sepat, Kuantan, Pahang. Using bivalves as bio-indicators, the objectives of this study are to determine the level of concentration of Copper (Cu), Zinc (Zn), Cadmium (Cd) and Lead (Pb), and to evaluate these concentrations according to the permissible limits established by the Malaysia Food Act (1983) and Food Regulations (1985) and the World Health Organisation (1982). Before analysing the samples with Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES), the collected and desiccated samples were digested with acid. The concentrations of copper (Cu), zinc (Zn), cadmium (Cd), and lead (Pb) were determined to be 0.56 ppm, 6.76 ppm, 0.06 ppm, and 0.04 ppm, respectively. The order of metals in the collected Meretrix spp. is Zn> Cu> Cd> Pb. The concentrations of all elements present in the hard clams were assessed and found to fall within acceptable thresholds, indicating that they are suitable for consumption without posing any health risks.